Substituted benzoquinazolinones. Part 2: Synthesis of amino-, and sulfanyl-derivatives of benzo[f]- and benzo[h]quinazolinones. Issue 50 (16th December 2015) - Nowak, Monika; Malinowski, Zbigniew; Fornal, Emilia; Jóźwiak, Andrzej; Parfieniuk, Ewa; Gajek, Gabriela; Kontek, Renata
Abstract: Amino- and sulfanyl-derivatives of benzoquinazolinones16a –c, 20a –c and21a –c were prepared under palladium-catalyzed Buchwald–Hartwig coupling reaction using bromobenzoquinazolinones15, 19a, 19b and 1-substituted piperazines or mercaptans. The combination of Pd(OAc)2 with XantPhos proved to be the best for these conversions in the presence of KO t -Bu, in 1, 4-dioxane as a solvent, at 90–100 °C. The 8-bromobenzo[ f ]quinazolin-1(2 H )-one15 was synthesized via condensation of the ethyl or tert -butyl 2-amino-8-bromonaphthalene-1-carboxylate6, 10 with formamide, followed by reaction with 3, 4-dimethoxybenzyl bromide. However, the 6-bromobenzo[ h ]quinazolin-4(3 H )-ones19a, 19b were prepared from ethyl 4-bromo-1-[( tert -butoxycarbonyl)amino]naphthalene-2-carboxylate (17 ). Biological screening of the potential cytotoxicity of compounds16a, 20a, 20c on HT29 and HCT116 cell lines, has shown that compound20a has a significant anticancer activity. Graphical abstract: